Analysis of the flow conditions between the bottoms of the ship and of the waterway. (1st March 2020) - Böttner, Carl-Uwe; Anschau, Pascal; Shevchuk, Ivan
Abstract: A physical model test was performed, to which a scaled model (1:40) was designed and constructed to carry two Laser Doppler Velocimetry sensors and provide optical access at different locations along the hull to detect the stream close to bottom of the hull and resolving the boundary layer flow at the hull. The measurement campaign was conducted in a shallow water towing tank and included a range of water depths and ship speeds such that the influence of each became analysable. The purpose of the experiment is to provide validation data to further corroborate a numerical approach and to gain deeper insight in the flow conditions in the gap flow underneath the vessel in very shallow water. In addition the extension of the effect of propulsion on the dynamic sinkage and trim in very shallow water was checked. Even though for one particular ship design and restricted to model scale 1:40, the results are regarded a valuable basis for further investigations on this phenomenon. Highlights: Towing tank model tests in shallow water with optical flow measurements. Gap Flow between ship bottom and tank analysed. Boundary layer resolved along the keel plate by laser doppler velocimetry. Boundary layer is increasing with decreasing under keel clearance. Propulsion impact on dynamic sinkage and trim in very shallow water detected.